Non-radio communication using mobile devices (screen-camera communication) - Toh, Esther Sin Rong (2015)
This project aims to provide a new way of sending data such as images and text files through mobile devices without existing technologies such as WiFi, Bluetooth and Cellular Data Network. This application, ColorQR aims to send text files and images through the use of colors and camera and enable QR to send more data and at a higher throughput. Data is encoded into Red, Blue and Green colors QR code and are multiplexed to form multiple 1 multi-color QR code that will be flashed on the device screen. Then a camera will be used to video record the flashing images and convert the images into RGB channels using grayscale conversion. Thus 1 image will be split to 3 black and white QR codes. Finally, it is able to decode the image and text file that are sent. Several testing were done to find the decoding speed and accuracy among 4 devices and results show that LG Nexus 4 performs the best and has a decoding accuracy of 100% when sending text files. Different transmission rates are also experimented to find out if it will affect the decoding accuracy and results show that for Samsung devices, the faster the transmission rate, the lower decoding accuracy it gets. Encoding speed test was performed as well.